Procedure for the Selection among Technologies. Treatment of Deodorizer Distillate Oil - Laoretani, Daniela Soledad (2014)
With the aim of both adding value by recovering tocopherols from a natural source and promoting environmental care, this work studies how to select among available technological alternatives for the processing of deodorizer distillate oil (DDO), which is a residue of the edible oils refining industry. The work focuses on how to generate a first set of promising alternatives (we propose to follow an established process design procedure based on heuristics, combined with a screening of the literature, with criteria to narrow the large number of alternatives published). The final selection among them is an established approach: we propose to implement a multiobjective optimization mixed integer linear program maximizing the net present value (NPV) and minimizing the generation of greenhouse gases measured as kilogram-equivalent of CO2. For a given case study of soybean DDO the first step generated a set of six technologies for the treatment of DDO with different processing capacities plus two additional alternatives for the final destination of DDO. The Pareto set of solutions constructed with the results provides information to adopt a both economic and environmentally sound choice of a processing technology. For the particular case analyzed, the technology that maximizes NPV within the Pareto set of solutions was esterification of free fatty acids with ethanol in acid medium followed by a separation of the esters by molecular distillation, at the largest production capacity (576,000 kg/year). This technology gives the maximum NPV of $19,574,000 generating 5,142,500 kg of CO2-equiv. The results obtained are useful for decision making in the industry, to give an adequate final destination to the residue DDO.